Effects of different phenolic compounds on the oxidative stability of myofibrillar proteins after in vitro metal-catalyzed oxidation - Yuqi Wu; Wenhui Wang; Yanan Zhao; Qimeng Sun; Jinfeng Pan; Xiuping Dong; Shengjie Li (Food Science of Animal Products, 2025)
This study aimed to investigate the effects of several common phenolic compounds on protein oxidation of myofibrillar protein after in vitro metal-catalyzed oxidation. Suspensions of pig myofibrillar proteins containing one of the three phenolic compounds, chlorogenic acid (CA), gallic acid (GA), or epigallocatechin gallate (EGCG) were oxidized for 24 h using a Fenton oxidation system. Suspensions with butylated hydroxytoluene and a group with no phenolic compounds were considered as control. Various markers for protein oxidation were measured, including total carbonyl, total sulfhydryl and free sulfhydryl, total free amino group, and particularly, two specific markers for protein carbonylation, namely, α-amino adipic semialdehyde (AAS) and lysinonorleucine (LNL) were also determined. Meanwhile, protein solubility, circular dichroism spectrum, and tryptophan fluorescence were also analyzed for the consequences of protein oxidation. Results showed that all three plant polyphenols exhibited a significant inhibitory effect on carbonyl formation. Concurrently, these plant polyphenols engaged in addition reactions with myofibrillar proteins, leading to a reduction in the levels of total sulfhydryl and free amino groups. This reduction further influences the alterations in the secondary and tertiary structures of the proteins. Consequently, the levels of carbonyls and AAS content in proteins may serve as more precise indicators of the antioxidant capacity of polyphenols in meat products in comparison to sulfhydryl content. It’s worth stating that EGCG exhibits a unique ability to promote the formation of AAS, distinguishing it from other plant polyphenols.